2018
DOI: 10.1111/myc.12816
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of fungaemia in Sweden: A nationwide retrospective observational survey

Abstract: We report an overall increase in candidaemia but a minor decrease of C. albicans while C. glabrata and C. parapsilosis remain constant over this 10-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 26 publications
(36 reference statements)
2
35
0
1
Order By: Relevance
“…In a previous study, we reported the incidence of candidaemia as 4.2/100 000 inhabitants in 2005‐2006 . We reported recently an increased incidence . The incidence of candidemia has been increasing worldwide.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…In a previous study, we reported the incidence of candidaemia as 4.2/100 000 inhabitants in 2005‐2006 . We reported recently an increased incidence . The incidence of candidemia has been increasing worldwide.…”
Section: Discussionmentioning
confidence: 92%
“…Candidemia data were derived from the latest data from national epidemiological fungemia surveillance programme. The incidence of candidemia is 4.7/100 000 individuals in Sweden . The number of cases with intra‐abdominal candidiasis ( Candida peritonitis), usually a postsurgical complication was also seen only in intensive care unit at a rate of 50% of the candidemia cases based on previous study .…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations